Economic, demographic and political determinants of pollution reassessed: A sensitivity analysis - Martin Gassebner; Michael Lamla; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2006)
Recent literature proposes many variables as significant determinants of pollution. This paper gives an overview of this literature and asks which of these factors have an empirically robust impact on water and air pollution, i.e. do not depend upon the conditioning information set. For this, we apply Extreme Bound Analysis (EBA) on a panel of 208 countries covering the period 1960-2001. We find supportive evidence on the existence of the environmental Kuznets curve. Furthermore, mainly demographic variables and variables capturing the economic structure of a country contribute in explaining air and water pollution.
Keywords: C52; F18; L60; O13; Q53; 330; pollution; environment; sensitivity analysis; environmental Kuznets curve; Umweltbelastung; Wirtschaftsstruktur; Bevölkerungsentwicklung; Sensitivitätsanalyse; Panel; Environmental Kuznets Curve